Micro-magnetic characterisation of ground AISI D2 tool steel using hysteresis loop technique. (14th May 2021) - Awale, Akash; Shrivastava, Atul Kumar; Chaudhari, Abhimanyu; Vashista, Meghanshu; Yusufzai, Mohd Zaheer Khan
According to tooling industries, grinding is the most effective and economical machining for AISI D2 tool steel owing to its low thermal conductivity. The first objective is to investigate the effect of grinding environments on surface integrity of AISI D2 tool steel. Grinding performance like force ratio and grinding temperature was investigated under wet and dry environments. The second objective is to qualitatively assess the thermal damage of ground surface using non-destructive hysteresis loop (HL) technique. The result shows that higher force ratio and surface roughness were obtained under flood grinding. Maximum thermal damage in terms of drastic variation in microstructure and microhardness were observed under dry grinding owing to serious plastic deformation at higher grinding temperature. HL outcomes like lower average permeability, higher coercivity and remanence were obtained with higher thermal damage on ground surface. Finally, linear correction was obtained between HL outcomes and microhardness of ground samples.